The Development of Canva-Assisted Problem Based Learning Media to Improve Students’ Critical Thinking Skills and Digital Literacy on Elementary School - Intan Fattimah; Heris Hendriana; Galih Dani Septiyan Rahayu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
The mathematical critical thinking skills and digital literacy of elementary school students are still not optimally developed, while the demands of 21st century learning require the mastery of these two competencies in an integrated manner. This research aims to develop a Problem Based Learning  learning model with interactive Canva media to improve the mathematical critical thinking and digital literacy skills of grade V elementary school students. This research uses a Research and Development (R&D) approach with the Borg and Gall model which is modified into seven stages, namely preliminary research, planning, product development, expert validation, revision, field trials, and product refinement. The research subjects consisted of 60 grade V students at SD Al-Ikhlas and SD Cemara who were selected through purposive sampling techniques. The research instruments include expert validation sheets, critical thinking ability tests (pretest-posttest), digital literacy observation sheets, and student response questionnaires. Data analysis used descriptive statistics as well as the nonparametric tests of the Wilcoxon Signed-Rank Test and Mann-Whitney because the data were not entirely distributed normally based on the Shapiro-Wilk test. The results of expert validation showed that the model obtained a very decent category with an average score of 4,510 out of a scale of 5.0. Mathematical critical thinking skills increased significantly from an average of  47.90 pretest to  a posttest of 77.58 with an N-gain value of 0.567 in the medium category and a significance of 0.000. Students' digital literacy reached an average of 16.87 from a maximum score of 20, while student responses showed a positive category with an average of 4.187 out of a scale of 5.0. The Problem Based Learning  model with interactive Canva media has proven to be feasible, effective, and practical as an innovative learning alternative based on the Technological Pedagogical Content Knowledge  framework to improve the mathematical critical thinking skills and digital literacy of elementary school students.